Primary hyperoxaluria type 1: A literature review upon three clinical cases - Leal,Rita (2014)
Primary hyperoxaluria type 1 is a rare metabolic disorder of the hepatic peroxisomes characterised by excessive oxalate production, kidney deposition and subsequent systemic oxalosis. The diagnosis is often delayed and about 30% of the patients have end-stage renal disease at the time of diagnosis. The recommended treatment when there is end-stage renal disease is combined liver and kidney transplantation, bridging the hepatic enzyme defect and renal dysfunction. We report three cases of young women with primary hyperoxaluria type 1 and end-stage renal disease, making a subsequent systematic review of this topic. The timing of diagnosis and, consequently, the start of therapy were different for the three patients and may have an impact on prognosis. Since it is such a rare disease, the diagnosis is dependent on a strong clinical suspicion. In patients with a history of nephrocalcinosis and/or recurrent nephrolithiasis with progression to chronic kidney disease, this diagnosis should be excluded, especially before considering an isolated kidney transplant